Higher order thinking skills-based reading literacy assessment instrument: An Indonesian context - Damaianti, Vismaia Sabariah; Abidin, Yunus; Rahma, Rosita (Universitas Pendidikan Indonesia, 2020)
Learning theories have seen the development of students’ higher order thinking skills a quintessential educational goal for all students, as the absence of such skills in learning leads to students’ difficulty in answering questions that are analytical, critical, creative, and problem-solving. What is more, the prevailing literacy scoring instruments have yet to take into account the Indonesian cultural context despite the fact that culture is such an important vehicle in strengthening the identity of a nation. In order to address this problem, employing a research-and-development method, a HOTS-based reading literacy scoring device model was proposed in this research. In the development stage, the model was tested to 476 junior high school students in two separate islands in Indonesia: Java and Bali. The results of the qualitative assessment from the experts showed that the product developed in principle had fulfilled the requirements. Meanwhile, the validity and reliability test results demonstrated that the instrument under investigation had met the requirements as a standardized reading literacy assessment product. Implicationally, therefore, the proposed model can be utilized in assessing students’ reading skill in Indonesian contexts.